2014
DOI: 10.1097/shk.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Place for Crystalloids and Colloids in Remote Damage Control Resuscitation?

Abstract: Crystalloids and colloids are used in prehospital fluid resuscitation to replace blood loss and preserve tissue perfusion until definite surgical control of bleeding can be achieved. However, large volumes of fluids will increase bleeding by elevating blood pressure, dislodging blood clots, and diluting coagulation factors and platelets. Hypotensive fluid resuscitation strategies are used to avoid worsening of uncontrolled bleeding. This is largely supported by animal studies. Most clinical evidence suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Proper discussion of this is outside the scope of this review. Suffice it to say that the use of dextrans clinically is limited by a significant incidence of anaphylactoid reactions (Lundsgaard-Hansen, 1969 ; Medby, 2014 ) and coagulopathy due to interference with some of the clotting factors (Hahn, 2013 ; Medby, 2014 ) although this property has been put to good use in prevention and treatment of deep vein thrombosis (Medby, 2014 ). In animal experiments it was shown that release of histamine and 5-hydroxytryptamine occurs from mast cell degranulation as also reported for HRP (see above).…”
Section: More Appropriate Markers Of Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…Proper discussion of this is outside the scope of this review. Suffice it to say that the use of dextrans clinically is limited by a significant incidence of anaphylactoid reactions (Lundsgaard-Hansen, 1969 ; Medby, 2014 ) and coagulopathy due to interference with some of the clotting factors (Hahn, 2013 ; Medby, 2014 ) although this property has been put to good use in prevention and treatment of deep vein thrombosis (Medby, 2014 ). In animal experiments it was shown that release of histamine and 5-hydroxytryptamine occurs from mast cell degranulation as also reported for HRP (see above).…”
Section: More Appropriate Markers Of Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…The most commonly used resuscitation fluids have been blood, saline, or lactated Ringer’s, but colloids have also been used. There is active clinical discussion about the merits and detriments of each fluid type and also about when and how much resuscitation is ideal (55). Other important protocol issues include the presence or absence of anesthesia, which can affect hemodynamic, neurological, and other physiological responses, as well as the use of anticoagulants such as heparin (Table 3) (49).…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 99%
“…Medby (7), Norwegian Armed Forces Medical Services, provides a balanced overview of the current status and understanding of the benefits and risks of both crystalloids and colloids. Medby (7), Norwegian Armed Forces Medical Services, provides a balanced overview of the current status and understanding of the benefits and risks of both crystalloids and colloids.…”
Section: Prehospital Fluid Resuscitationmentioning
confidence: 99%